Perancangan Sistem Informasi Penggajian Karyawan Studi kasus : STMIK Sinar Nusantara Surakarta - andriani kusumaningrum (STMIK Sinar Nusantara, 2010)
Data collection methods include: methods of literature study conducted by the research literature relevant to the problems faced to obtain precise and accurate data for the perfection of the system are made.The results of this research is a design of information systems in the form of system design in this study are data flow diagrams, Database Design and menu scheme. Keywords : design, information system, payroll